Seeing A Buddhist Doing Business: An Interview with Sudhamek AWS - Yulianti, Yulianti (Faculty of Islamic Economics and Business, Institut Agama Islam Negeri (IAIN) Surakarta, 2018)
This paper discusses an interview with Sudhamek AWS, a well-known Buddhist businessman in Indonesia. Through this interview, the author of this article confidently examines how Sudhamek negotiated the practices of Buddhism and business. The author has conducted a structured interview with Sudhamek directly. Having conducting an interview, the author argues that as a businessman, Sudhamek is not just a businessperson but he is a Buddhist who tries to put his understanding of religion into practice especially related to his way of life. This interview has a salient contribution for opening portray of business values in Indonesian businessman world today. Keywords: business, spiritual economics, Buddhism ethics